Memory Training Techniques for Simultaneous Interpretation - Bakhtiyor qizi, Sevara Sultonova (Central Asian Journal of Literature, Philosophy and Culture, 2022)
In the modern world, the role of intercultural and interethnic communication cannot be overestimated. The importance of the work of an interpreter as a mediator in conducting various bilateral or multilateral contacts is very significant. Sometimes issues of war and peace are resolved with the assistance of an interpreter. However, in their work, a professional translator can perform various types of translation to solve the task. The purpose of this work is to identify the grounds for classifying the types of translation, in particular, determining the place of simultaneous translation in the system of types of translation and considering the methods of memory training in simultaneous interpretation.